PERLINDUNGAN HUKUM TERHADAP KARYA ILUSTRASI DIGITAL YANG DIPUBLIKASI TANPA IZIN DALAM BENTUK NON-FUNGIBLE TOKEN (NFT) - Deviana Fadilah Bayhaqi, (2023)
Digital illustration is a type of work that is in great demand in the digital era and is easily disseminated through various platforms. Meanwhile, digital illustrations are a protected type of creation where the creator has exclusive rights in the form of moral and economic rights over the digital illustration work. This research aims to conduct a study related to legal protection for digitally illustrated works issued without permission in the form of Non-Fungible Tokens (NFT) as well as legal remedies that can be taken by creators in such cases. This study uses a qualitative research method through an approach to the provisions of Law Number 28 of 2014 concerning copyright. The results of this study indicate that digital illustrations are a type of creation that is protected by law, where the copyright law has regulated the protection of a creation from activities that have the potential to harm the creator, so that the activity of publishing digital illustrations without permission in the form of Non-Fungible Tokens is an act of copyright infringement that violates the moral and economic rights of the creator. Because of this, creators can take legal action in the form of preventive and repressive measures either through non-litigation or litigation to obtain recovery for rights that have been violated.